Therapeutic Medication Errors in the Non-Healthcare Facility Setting Associated with Hospital Admission, 2000–2024 - Srija Nuguri; Sandhya Kistamgari; Hannah L. Hays; Natalie I. Rine; Nichole L. Michaels; Motao Zhu; Gary A. Smith (Journal of Medical Toxicology, 2026)
Introduction This study investigated the characteristics and trends of therapeutic medication errors reported to United States (US) poison centers that occurred in a non-healthcare facility setting and were associated with hospital admission. Methods Using a retrospective cohort design, National Poison Data System data from 2000 to 2024 were analyzed. US Census Bureau data were used to calculate population-based rates. Results There were 115,071 therapeutic medication errors that occurred in a non-healthcare facility setting and were associated with hospital admission reported to US poison centers from 2000 to 2024. Most involved females (55.5%), individuals > 49 years old (56.9%), a single substance (71.5%), or occurred in a residence (96.0%). In addition, 39.0% were admitted to a critical care unit and 53.3% were associated with a serious medical outcome, including moderate effects (45.4%), major effects (7.2%), or death (0.7%, n = 745). Cardiovascular drugs (24.7%), analgesics (18.2%), and antidepressants (11.3%) were most commonly involved. The overall hospitalized therapeutic medication error rate per one million US population increased by 196.9% from 7.06 in 2000 to 20.97 in 2024; the rate was highest among adults > 69 years old, females, and errors involving cardiovascular drugs. Of the 115,009 exposures in which at least one therapeutic medication error scenario was reported, the most common scenarios were “other incorrect dose” (23.6%), “wrong medication taken/given” (16.7%), and “inadvertently took/given medication twice” (13.9%). Conclusions These study findings highlight opportunities to strengthen prevention efforts targeting therapeutic medication errors, particularly among older adults and individuals using cardiovascular medications, which could meaningfully decrease associated morbidity, mortality, and healthcare costs.

Impact of advanced cloud microphysics schemes for the Kerala flood events in 2018 and 2019 using the NCMRWF regional model - Rose Raphel; A. Jayakumar; T.J. Anurose; Saji Mohandas; Greeshma M. Mohan; M. Sandhya; Anumeha Dube; Donali Gogoi; V.S. Prasad; Claudio Sanchez (Atmospheric Research, 2026)

Enhanced glyphosate biodegradation by heavy metal-tolerant microbial consortium QLBS in co-contaminated environment: Kinetics and metabolic pathways - Zeren Li; Mengyi Chen; Ziye Chen; Wen-Juan Chen; Mingqiu Liu; Guiling Si; Haoran Song; Huijie Zhou; Zhenyu Zhang; Bin Liang; Sandhya Mishra; Mohamed A. Ghorab; et al. (Journal of Cleaner Production, 2026)

Improving lightning representation in global model through convective cloud based Price and Rind 1992 scheme - M. Sandhya; Greeshma M. Mohan; Saji Mohandas; A. Jayakumar; T.J. Anurose; V.S. Prasad (Science of The Total Environment, 2026)

Comparison of Pediatric and Adult Glucagon-Like Peptide-1 Receptor Agonist Exposures Reported To United States Poison Centers, 2017–2024 - Anjali Senthilkumar; Hannah L. Hays; Sandhya Kistamgari; Natalie I. Rine; Allison L. Rhodes; Christopher E. Gaw; Gary A. Smith (Journal of Medical Toxicology, 2026)
Introduction As glucagon-like peptide-1 receptor agonist (GLP-1) use has increased among children, a better understanding of the related adverse effects in this population is needed. Methods National Poison Data System data from 2017 to 2024 were analyzed to compare characteristics and trends of exposures involving GLP-1s reported to United States (US) poison centers (PCs) among children 6–17 years old with those of adults. Results There were 13,924 single-substance GLP-1 exposures reported to US PCs from 2017 to 2024. The rate of exposures per one million US population increased by 1,830.8% from 0.97 in 2017 to 18.79 in 2024, including a 4,805.0% increase among children 6–17 years old from 0.04 in 2017 to 1.97 in 2024, with the majority of the increase occurring after 2021. Most exposures (91.7%) were associated with no or mild effects, while moderate effects were observed in 8.0% and major effects occurred in 42 exposures; there were two deaths. Children 6–17 years old were more likely (RR: 2.66, 95% CI: 1.73–4.11) to be admitted than adults, and children 12–17 years old were more likely (RR: 1.68, 95% CI: 1.08–2.63) to experience a more serious medical outcome than adults. Children 6–17 years old with at least one clinical effect experienced vomiting (88.2%) more commonly than adults (61.3%) (RR: 1.44, 95% CI: 1.34–1.55). Additionally, exposures among children 6–17 years old were more likely to be attributable to intentional misuse (RR: 8.12, 95% CI: 6.47–10.17) than among adults. Conclusions This study provides national-level, real-world findings that may help inform clinical practice.

Unveiling the novel biodegradation mechanisms of acephate by Pandoraea pnomenusa: Catalytic pathway, functional enzyme, and environmental bioremediation - Ziqiu Lin; Mingqiu Liu; Shimei Pang; Wen-Juan Chen; Sandhya Mishra; Mohamed A. Ghorab; Shaohua Chen (Bioresource Technology, 2026)

Bacillus subtilis as a powerful weapon in the removal of environmental pollutants - Mingqiu Liu; Wen-Juan Chen; Guiling Si; Chenxi Yan; Haoran Song; Sandhya Mishra; Mohamed A. Ghorab; Shaohua Chen (Journal of Environmental Management, 2025)

Biodegradation of the widely used amide herbicides: Microbial resources, catabolic pathways and molecular mechanisms - Guiling Si; Quanhong Zhang; Mingqiu Liu; Wen-Juan Chen; Yuting Tong; Parul Chaudhary; Sandhya Mishra; Mohamed A. Ghorab; Shaohua Chen (Journal of Environmental Management, 2025)

LP-53 Evaluation of the Mutagenic Potential of 1-Cyclopentyl-4-Nitrosopiperazine Nitrosamine in Human Lymphoblastoid TK6and CHO-K1 Cells - M. Shameer P; T. Pradeep; M. Rajini; A. Mariappan; S. Sandhya; G. Kulavardhan; M. Sumithra; R. Harika; A. Varun; K. Mohan; V. Deepa (Toxicology Letters, 2025)

Revealing drought tolerance mechanisms in Pongamia pinnata through integrated physiological, biochemical, and transcriptomic profiling - K. Rajarajan; Sandhya Sharma; Harsha Srivastava; Kumari Arpita; A.K. Handa; A. Arunachalam; S.K. Dhyani (Plant Gene, 2025)

Cultivation of Scenedesmus obliquus NCIM 5526 in a sol–gel transition medium for lipid production - V Varshini; R V Anusha Gowri; S Sandhya; L A Nirmal; S Jacob (International Journal of Environmental Science and Technology, 2025)

Marine Life Ecosystem Analysis Based on Climate Change Detection Using Deep Learning Algorithms - B. Rebecca; A. Sandhya; Kiran Sree Pokkuluri; Gunipati Kanishka; Khasimbee Shaik; B. Murali Krishna (Remote Sensing in Earth Systems Sciences, 2025)

On the role of Sri Lankan land mass in safeguarding the southeastern coast of India from Southern Ocean swell attacks - K G Sandhya; R Harikumar; P A Francis; Balaji Baduru; T M Balakrishnan Nair (Journal of Earth System Science, 2025)

Microplastics in agricultural soils following sewage sludge applications: Evidence from a 25-year study - Stuart J.F.F. Ramage; Malcolm Coull; Patricia Cooper; Colin D. Campbell; Radhakrishna Prabhu; Kyari Yates; Lorna A. Dawson; Sandhya Devalla; Eulyn Pagaling (Chemosphere, 2025)

Pediatric Exposures Associated with Caffeine Energy Products Reported to United States Poison Centers, 2011–2023 - Timothy R. Thompson; Hannah L. Hays; Sandhya Kistamgari; Natalie I. Rine; Motao Zhu; Henry Xiang; Gary A. Smith (Journal of Medical Toxicology, 2025)
Introduction This study investigated the characteristics and trends of pediatric exposures to caffeine energy products reported to US poison centers Methods National Poison Data System data for caffeine energy product single-substance exposures during 2011–2023 among individuals < 20 years old were analyzed. Results There were 32,482 caffeine energy product exposures reported to US poison centers with a 17.3% exposure rate increase during 2011–2023. Most exposures were among < 6-year-olds (69.6%), males (56.7%), or involved liquid formulations (57.5%). Most (80.7%) were not treated in a healthcare facility; however, 1.6% were medically admitted. Teenagers 13–19 years old were more likely to be medically admitted (OR = 12.74, 95% CI: 10.40–15.60) or have a serious medical outcome (OR = 18.83, 95% CI: 16.88–21.01) than children < 13 years old. Solid energy product formulations were more likely to be associated with a serious medical outcome (OR = 1.98, 95% CI: 1.81–2.17) or medical admission (OR = 5.23, 95% CI: 4.31–6.36) than other types of formulations. During the study period, exposure rates increased for liquid (34.5%) and powder/granules (632.9%) product formulations but decreased for solids (-51.5%). Among liquid formulation subcategories, the exposure rate for beverages increased (46.5%) and that for shots decreased (-86.1%). Conclusions Although most pediatric exposures to caffeine energy products reported to US poison centers were associated with no or minimal clinical effects, serious medical outcomes and medical admissions occurred. The product formulations that drove the 17% increase in the exposure rate changed during the study period. Opportunities exist to reduce the adverse effects of caffeine energy products among the pediatric population.

Evaluating the effects of zinc oxide nanoparticles on a sentinel aquatic invertebrate species: Transcriptomic analysis and potential implications for ecosystem health - V.G. Vysakh; Sandhya Sukumaran; A. Gopalakrishnan (Marine Pollution Bulletin, 2025)

Unveiling the hydrolase Oph2876 mediated chlorpyrifos degradation mechanism in Pseudomonas nitroreducens and its potential for environmental bioremediation - Haoran Song; Wen-Juan Chen; Shao-Fang Chen; Mingqiu Liu; Guiling Si; Xixian Zhu; Kalpana Bhatt; Sandhya Mishra; Mohamed A. Ghorab; Shaohua Chen (Journal of Hazardous Materials, 2025)

Mechanistic insights into D-cyphenothrin biodegradation by Rhodococcus ruber Y14 and its potential for bioremediation of pyrethroid-polluted environment - Yaohua Huang; Shunkang Zhou; Wen-Juan Chen; Xiaofan Zhou; Shao-Fang Chen; Haoran Song; Zhenchen Yan; Sandhya Mishra; Mohamed A. Ghorab; Pankaj Bhatt; Shaohua Chen (Chemical Engineering Journal, 2025)

Removal of alachlor from the water/soil environments: The significance of microbial remediation and its biochemical mechanisms - Zeren Li; Mengyi Chen; Wen-Juan Chen; Mingqiu Liu; Guiling Si; Xixian Zhu; Kalpana Bhatt; Sandhya Mishra; Mohamed A. Ghorab; Shaohua Chen (Journal of Water Process Engineering, 2024)

Complete biodegradation of glyphosate with microbial consortium YS622: Structural analysis, biochemical pathways, and environmental bioremediation - Wenping Zhang; Wen-Juan Chen; Shao-Fang Chen; Mingqiu Liu; Mohamed A. Ghorab; Sandhya Mishra; Pankaj Bhatt; Shaohua Chen (Journal of Environmental Chemical Engineering, 2024)

Silver nanoparticle-induced in vitro flowering in Dendrocalamus strictus (Roxb.) nees and genetic fidelity assessment of regenerants using molecular markers - Bharat Singh Rajput; M. Manokari; Nitin J. Solanki; Dulam Sandhya; Mohammad Faisal; Abdulrahman A. Alatar; Mahipal S. Shekhawat (Molecular Biology Reports, 2024)

Removal of chlorimuron-ethyl from the environment: The significance of microbial degradation and its molecular mechanism - Haoran Song; Wen-Juan Chen; Shao-Fang Chen; Xixian Zhu; Sandhya Mishra; Mohamed A. Ghorab; Pankaj Bhatt; Shaohua Chen (Chemosphere, 2024)

Glucagon-Like Peptide-1 Receptor Agonist Cases Reported to United States Poison Centers, 2017–2022 - Christopher E. Gaw; Hannah L. Hays; Cydney A. Kemp; Sandhya Kistamgari; Henry A. Spiller; Natalie I. Rine; Allison L. Rhodes; Motao Zhu; Gary A. Smith (Journal of Medical Toxicology, 2024)
Introduction Glucagon-like peptide-1 receptor agonists (GLP-1RAs) are a class of medications for management of diabetes and obesity. The objective of this study is to characterize the epidemiology of GLP-1RA cases reported to US poison centers. Methods We analyzed cases involving a GLP-1RA reported to the National Poison Data System during 2017–2022. Results There were 5,713 single-substance exposure cases reported to US poison centers involving a GLP-1RA. Most cases were among females (71.3%) and attributable to therapeutic errors (79.9%). More than one-fifth (22.4%) of cases were evaluated in a healthcare facility, including 0.9% admitted to a critical care unit and 4.1% admitted to a non-critical care unit. Serious medical outcomes were described in 6.2% of cases, including one fatality. The rate of cases per one million US population increased from 1.16 in 2017 to 3.49 in 2021, followed by a rapid increase of 80.9% to 6.32 in 2022. Trends for rates of serious medical outcomes and admissions to a healthcare facility showed similar patterns with 129.9% and 95.8% increases, respectively, from 2021 to 2022. Conclusions Most GLP-1RA cases reported to US poison centers were associated with no or minimal effects and did not require referral for medical treatment; however, a notable minority of individuals experienced a serious medical outcome or healthcare facility admission. The rate of reported cases increased during the study period, including an 80.9% increase from 2021 to 2022. Opportunities exist to improve provider and patient awareness of the adverse effects of these medications.

Silver doped barium titanate nanoparticles for enhanced visible light photocatalytic degradation of dyes - A. Bhava; U. Sandhya Shenoy; D. Krishna Bhat (Environmental Pollution, 2024)

Bioactive activity and safety analysis of Monascus red biopigment - Vishu Chaudhary; Priya Katyal; Jaspreet Kaur; Surekha Bhatia; Sandhya Singh; Anuj Kumar Poonia; Anil Kumar Puniya; António Raposo; Sunghoon Yoo; Heesup Han; Hmidan A. Alturki; Anil Kumar (Food Bioscience, 2024)

The Phylogenetic Study of the CRISPR-Cas System in Enterobacteriaceae - Simran Krishnakant Kushwaha; Aryahi A. Kumar; Hardik Gupta; Sandhya Amol Marathe (Current Microbiology, 2023)

Pediatric Suspected Suicides and Nonfatal Suicide Attempts Reported to United States Poison Control Centers Before and During the COVID-19 Pandemic - Hailee R. Ciccotti; Henry A. Spiller; Marcel J. Casavant; Sandhya Kistamgari; Alexandra R. Funk; Gary A. Smith (Journal of Medical Toxicology, 2023)

Intracellular trehalose modulates oxidative responses and dehydrin gene expression in Arabidopsis thaliana (L.) Heynh during dehydration - Akhil Mohanan; Sandhya Gandhi; Noor Al Ain A; Dinakar Challabathula (Brazilian Journal of Botany, 2023)

Recent advances in Surface Plasmon Resonance (SPR) biosensors for food analysis: a review - Nevetha Ravindran; Sandhya Kumar; Yashini M; Rajeshwari S; Mamathi C A; Nirmal Thirunavookarasu S; Sunil C K (Critical Reviews in Food Science and Nutrition, 2023)

Population genetic research on the Spadenose shark, Scoliodon laticaudus (Chondrichthyes, Carcharhinidae), reveals the presence of two significantly differentiated clades along the Indian coast - Sandhya Sukumaran; Wilson Sebastian; P. U. Zacharia; Shoba J. Kizhakudan; K. V. Akhilesh; Sujitha Thomas; Subal Kumar Roul; M. Muktha; Swati Priyanka Sen; G. B. Purushottama; Shikha Rahangdale; K. K. Bineesh; et al. (Marine Biodiversity, 2023)

Ghost fishing capacity of lost experimental gillnets: a preliminary study from Indian waters - Saly N. Thomas; Sandhya Kavitha Mandhir; Harsha Krishnankutty; Mary Baby K. A.; Aishwarya Ghosh K. A. (Environmental Science and Pollution Research, 2023)

Exome sequencing and microarray identified a novel large exonic deletion in SYT2 gene in an ultra-rare case with recessive CMS type 7 - C. P. Ravi Kumar; Parag M. Tamhankar; Radhika Manohar; Sheetal Sharda; G. K. Madhavilatha; S. G. Thenral; Sandhya Nair; A. K. Bojamma (Journal of Genetics, 2022)

Assessment of molecular genetic diversity of 384 chickpea genotypes and development of core set of 192 genotypes for chickpea improvement programs - Humara Fayaz; Asma Hamid Mir; Sandhya Tyagi; Aijaz A. Wani; Nelofar Jan; Mohammad Yasin; Javid Iqbal Mir; Biswajit Mondal; Mohd Anwar Khan; Reyazul Rouf Mir (Genetic Resources and Crop Evolution, 2022)

Sedimentological responses to coastal dynamics along the Thane District, North Maharashtra, West Coast of India - Sridhar D. Iyer; A. R. Gujar; V. Sanil Kumar; D. K. Naik; S. S. Gaonkar; Sandhya Naik; Pooja Shirodkar; F. Badesab; R. A. A. Luis (Sustainable Water Resources Management, 2021)

The signals of selective constraints on the mitochondrial non-coding control region: insights from comparative mitogenomics of Clupeoid fishes - Wilson Sebastian; Sandhya Sukumaran; A. Gopalakrishnan (Genetica, 2021)

ZnO nanoparticles for photodegradation of humic acid in water - Sandhya Babel; Putri A. Sekartaji; Hanggara Sudrajat (Environmental Science and Pollution Research, 2021)

Population genetic structure of the oceanic whitetip shark, Carcharhinus longimanus, along the Indian coast - S. Sreelekshmi; Sandhya Sukumaran; T. G. Kishor; Wilson Sebastian; A. Gopalakrishnan (Marine Biodiversity, 2020)

Status of Hilsa Fishery in Hooghly-Bhagirathi River System and Associated Coastal Waters of Northern Bay of Bengal - A. M. Sajina; V. R. Suresh; K. M. Sandhya; J. Mukherjee; R. K. Manna; B. K. Behera; R. Samanta; T. Maity; S. K. Banik (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2020)

Characterization of the Whole Mitogenome of Largehead Hairtail Trichiurus lepturus (Trichiuridae): Insights into Special Characteristics - Lakshmi P. Mukundan; Sandhya Sukumaran; Wilson Sebastian; A. Gopalakrishnan (Biochemical Genetics, 2020)

Molecular analyses reveal a lack of genetic structuring in the scalloped hammerhead shark, Sphyrna lewini (Griffith & Smith, 1834) along the Indian coast - Sandhya Sukumaran; Wilson Sebastian; Lakshmi P. Mukundan; Muktha Menon; K. V. Akhilesh; P. U. Zacharia; A. Gopalakrishnan (Marine Biodiversity, 2020)

Development and Investigation of Vitamin C-Enriched Adapalene-Loaded Transfersome Gel: a Collegial Approach for the Treatment of Acne Vulgaris - Sandhya Vasanth; Akhilesh Dubey; Ravi G.S.; Shaila A. Lewis; Vivek M. Ghate; Sally A. El-Zahaby; Srinivas Hebbar (AAPS PharmSciTech, 2020)

Contemporary and historic patterns of intraspecific diversity in Indian anchovy, Stolephorus indicus, from Indian peninsular waters - Sandhya Sukumaran; Wilson Sebastian; K. X. Francis; A. Gopalakrishnan (Genetica, 2019)

Isolation and phylogenetic identification of heterotrophic thraustochytrids from mangrove habitats along the southwest coast of India and prospecting their PUFA accumulation - K. V. Jaseera; P. Kaladharan; K. K. Vijayan; S. V. Sandhya; M. Leo Antony; M. A. Pradeep (Journal of Applied Phycology, 2019)

Spectral Modelling on the Characteristics of High Frequency Tail in Shallow Water Wave Spectra at Coastal Puducherry, East Coast of India - P. A. Umesh; Prasad K. Bhaskaran; K. G. Sandhya; T. M. Balakrishnan Nair (Pure and Applied Geophysics, 2019)

Event-Related Potentials in Response to Facial Affect Recognition in Patients with Schizophrenia - G. Sandhya; H. P. Prakash; K. R Nayak; R. V. Behere; P. R. Bhandary; A. S. Chinmay (Neurophysiology, 2019)

Isolation and characterization of Aquaporin 1 (AQP1), sodium/potassium-transporting ATPase subunit alpha-1 (Na/K-ATPase α1), Heat Shock Protein 90 (HSP90), Heat Shock Cognate 71 (HSC71), Osmotic Stress Transcription Factor 1 (OSTF1) and Transcription Factor II B (TFIIB) genes from a euryhaline fish, Etroplus suratensis - Wilson Sebastian; Sandhya Sukumaran; P. U. Zacharia; A. Gopalakrishnan (Molecular Biology Reports, 2018)

The complete mitochondrial genome and phylogeny of Indian oil sardine, Sardinella longiceps and Goldstripe Sardinella, Sardinella gibbosa from the Indian Ocean - Wilson Sebastian; Sandhya Sukumaran; P. U. Zacharia; A. Gopalakrishnan (Conservation Genetics Resources, 2018)

High Frequency Tail Characteristics in the Coastal Waters off Gopalpur, Northwest Bay of Bengal: A Nearshore Modelling Study - P. A. Umesh; Prasad K. Bhaskaran; K. G. Sandhya; T. M. Balakrishnan Nair (Pure and Applied Geophysics, 2018)

Re-description of the longtail butterfly ray, Gymnura poecilura (Shaw, 1804) (Gymnuridae: Myliobatiformes) from Bay of Bengal with a neotype designation - M. Muktha; K. V. Akhilesh; S. Sandhya; F. Jasmin; M. A. Jishnudev; Shoba Joe Kizhakudan (Marine Biodiversity, 2018)

Preclinical evaluation of the Aurora kinase inhibitors AMG 900, AZD1152-HQPA, and MK-5108 on SW-872 and 93T449 human liposarcoma cells - Sandhya Noronha; Lauren A. C. Alt; Taylor E. Scimeca; Omran Zarou; Justyna Obrzut; Brian Zanotti; Elizabeth A. Hayward; Akhil Pillai; Shubha Mathur; Joseph Rojas; Ribhi Salamah; Nalini Chandar; et al. (In Vitro Cellular & Developmental Biology - Animal, 2018)

Identification and comparative analysis of Brassica juncea pathogenesis-related genes in response to hormonal, biotic and abiotic stresses - Sajad Ali; Zahoor Ahmad Mir; Anshika Tyagi; Javaid A. Bhat; Narayanappa Chandrashekar; Pradeep Kumar Papolu; Sandhya Rawat; Anita Grover (Acta Physiologiae Plantarum, 2017)

Antibiotic Potential of Endophytic Actinomycetes of Medicinal Herbs Against Human Pathogenic Bacteria - Sandhya Chandrakar; A. K. Gupta (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2017)

Genetic population structure of Indian oil sardine, Sardinella longiceps assessed using microsatellite markers - Wilson Sebastian; Sandhya Sukumaran; P. U. Zacharia; A. Gopalakrishnan (Conservation Genetics, 2017)

Erratum to: De-oiled neem cake as potential bio-additive for low-salt raw skin preservation: a process for salinity reduction in tanneries - N. Vedaraman; K. V. Sandhya; V. Brindha; A. Tamil Selvi; K. C. Velappan; V. John Sundar; J. Kanagaraj; C. Muralidharan (International Journal of Environmental Science and Technology, 2016)

De-oiled neem cake as potential bio-additive for low-salt raw skin preservation: a process for salinity reduction in tanneries - N. Vedaraman; K. V. Sandhya; V. Brindha; A. Tamil Selvi; K. C. Velappan; V. John Sundar; J. Kanagaraj; C. Muralidharan (International Journal of Environmental Science and Technology, 2016)

AECHL-1, a novel triterpenoid, targets tumor neo-vasculature and impairs the endothelial cell cytoskeleton - Aparajita Dasgupta; Mithila A. Sawant; Manish S. Lavhale; Lakshmi-Surekha Krishnapati; Surendra Ghaskadbi; Sandhya L. Sitasawad (Angiogenesis, 2015)

Inorganic nanovectors for nucleic acid delivery - Sandhya Pranatharthiharan; Mitesh D. Patel; Anisha A. D’Souza; Padma V. Devarajan (Drug Delivery and Translational Research, 2013)

Contribution of GPR30 for 1,25 dihydroxyvitamin D3 protection in EAE - Sandhya Subramanian; Lisa M. Miller; Marjorie R. Grafe; Arthur A. Vandenbark; Halina Offner (Metabolic Brain Disease, 2012)

Sustained expression of circulating human alpha-1 antitrypsin reduces inflammation, increases CD4+FoxP3+ Treg cell population and prevents signs of experimental autoimmune encephalomyelitis in mice - Sandhya Subramanian; Galit Shahaf; Eyal Ozeri; Lisa M. Miller; Arthur A. Vandenbark; Eli C. Lewis; Halina Offner (Metabolic Brain Disease, 2011)

Recombinant TCR Ligand Reverses Clinical Signs and CNS Damage of EAE Induced by Recombinant Human MOG - Sushmita Sinha; Sandhya Subramanian; Ashley Emerson-Webber; Maren Lindner; Gregory G. Burrows; Marjorie Grafe; Christopher Linington; Arthur A. Vandenbark; Claude C. A. Bernard; Halina Offner (Journal of Neuroimmune Pharmacology, 2010)

Lysophosphatidylcholine induces inflammatory activation of human coronary artery smooth muscle cells - Nambi Aiyar; Jyoti Disa; Zhaohui Ao; Haisong Ju; Sandhya Nerurkar; Robert N. Willette; Colin H. Macphee; Douglas G. Johns; Stephen A. Douglas (Molecular and Cellular Biochemistry, 2007)

Elucidation of the lesions present in the transcription defectivefitA76 mutant ofEscherichia coli: Implication of phenylalanyl tRNA synthetase subunits as transcription factors - Sandhya Ramalingam; M. Hussain Munavar; S. Sudha; A. Ruckmani; R. Jayaraman (Journal of Biosciences, 1999)

Solid phase synthesis of combinatorial libraries using anhydrides as templates - John Perumattam; Sarvajit Chakravarty; Glenn A. McEnroe; R. Richard Goehring; Babu Mavunkel; Sandhya Suravajjala; Whitney W. Smith; Baili Chen (Molecular Diversity, 1997)